2008
DOI: 10.1124/jpet.107.133710
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Perfluorochemicals Improve Cell Survival during Reoxygenation by Pacifying Mitochondrial Activity

Abstract: Perfluorochemicals (PFCs) are known to provide a unique tool for controlled uptake and delivery of oxygen. We have characterized the effects of incremental oxygen delivery on cell viability of human ischemic cardiomyocytes using chemically inert PFCs as oxygen carrier. We have found that cell viability after prolonged ischemia depends on the dose of oxygen supplementation by oxygenated (ox) PFCs during reoxygenation. Although reoxygenation with the transient addition of oxPFCs in high concentrations (2250 M O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This result was consistent with previous findings after inhibition of oxidative phosphorylation (25). In addition, NO inhibition of ETC has been proven protective for the mitochondrial membrane potential (12), a phenomenon that we have shown previously for oxygen delivery (14). Thomas et al (26) demonstrated that NO inhibition of ETC might extend the zone of tissue oxygenation in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This result was consistent with previous findings after inhibition of oxidative phosphorylation (25). In addition, NO inhibition of ETC has been proven protective for the mitochondrial membrane potential (12), a phenomenon that we have shown previously for oxygen delivery (14). Thomas et al (26) demonstrated that NO inhibition of ETC might extend the zone of tissue oxygenation in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…In our previous paper, we presented information about cell viability of ischemic cardiomyocytes (14). The rationale for using cardiomyocytes after prolonged ischemia in this model was to understand why patients with myocardial infarction subjected to normoxic reperfusion after 12 h often do not experience complete myocardial salvage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations